Defoliation affects soybean yield depending on time and level of light interception reduction - Gregorutti, Viviana Carolina (2012)
Light interception during the critical period in soybean may be a better index of the injury level by defoliation than the insect population or the percentage of defoliation. Our aim was to simulate the effects of time and levels of defoliation on soybean seed yield, its numerical components and light interception during the critical period. The study was conducted in Paraná (31.5ºS; 60.3ºW), Argentina. We evaluated a combination of defoliation levels (0, 33, 66 and 100%) and two times of defoliation during soybean development (pod initiation and beginning of seed filling, i.e. R3 and R5, respectively). We measured radiation interception during the linear seed filling period (R5.5), seed yield and its components. Total defoliation performed at R3 reduced seed yield more than that performed at R5 (P<0.0001) (90% and 21% respectively, as compared to controls). Similarly, total defoliation performed at R3 reduced seed number by 85%, whereas that performed at R5 reduced seed number only by 3%, as compared to controls (P<0.0001). Seed yield and its components were significantly reduced when defoliation was applied at R3, because the radiation interception at R5.5 was reduced (P<0.001). Irrespective of the time of defoliation, PAR interception during the critical period (R5.5) was reduced only by total defoliation, evidencing the high vegetative plasticity of soybean. Our results provide a useful platform for the development of economic injury levels (EILs) based on light interception during the critical period.